RESULTS FROM THE XENON100 EXPERIMENT - Persiani, Rino (České vysoké učení technické v Praze, 2013)
The XENON program consists in operating and developing double-phase time projection chambers using liquid xenon as the target material. It aims to directly detect dark matter in the form of WIMPs via their elastic scattering off xenon nuclei. The current phase is XENON100, located at the Laboratori Nazionali del Gran Sasso (LNGS), with a 62 kg liquid xenon target. We present the 100.9 live days of data, acquired between January and June 2010, with no evidence of dark matter, as well as the new results of the last scientific run, with about 225 live days. The next phase, XENON1T, will increase the sensitivity by two orders of magnitude.